Improved search for invisible modes of nucleon decay in water with the SNO+ detector - SNO+ Collaboration (2022)
This paper reports results from a search for single and multi-nucleon disappearance from the $^{16}$O nucleus in water within the \snoplus{} detector using all of the available data. These so-called "invisible" decays do not directly deposit energy within the detector but are instead detected through their subsequent nuclear de-excitation and gamma-ray emission. New limits are given for the partial lifetimes: $τ(n→ inv) > 9.0×10^{29}$ years, $τ(p→ inv) > 9.6×10^{29}$ years, $τ(nn→ inv) > 1.5×10^{28}$ years, $τ(np→ inv) > 6.0×10^{28}$ years, and $τ(pp→ inv) > 1.1×10^{29}$ years at 90% Bayesian credibility level (with a prior uniform in rate). All but the ($nn→ inv$) results improve on existing limits by a factor of about 3.